2004
DOI: 10.5194/acp-4-439-2004
|View full text |Cite
|
Sign up to set email alerts
|

Volatile particles formation during PartEmis: a modelling study

Abstract: Abstract.A modelling study of the formation of volatile particles in a combustor exhaust has been carried out in the frame of the PartEmis European project. A kinetic model has been used in order to investigate nucleation efficiency of the H 2 O−H 2 SO 4 binary mixture in the sampling system. A value for the fraction ε of the fuel sulphur S(IV) converted into S(VI) has been indirectly deduced from comparisons between model results and measurements. In the present study, ε ranges between roughly 2.5% and 6%, de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…At high FSC levels the formation of volatile condensation particles with diameters D < 10 nm is observed (PETZOLD et al, 2003c). A kinetic model was used to investigate the nucleation efficiency of the H 2 O -H 2 SO 4 binary mixture in the exhaust gas and the particle coagulation processes during the transport through the sampling system to the measurement instrumentation (VANCASSEL et al, 2004). The model confirmed that the condensation particles form at the dilutor of the sampling system.…”
Section: Microphysical Propertiesmentioning
confidence: 91%
“…At high FSC levels the formation of volatile condensation particles with diameters D < 10 nm is observed (PETZOLD et al, 2003c). A kinetic model was used to investigate the nucleation efficiency of the H 2 O -H 2 SO 4 binary mixture in the exhaust gas and the particle coagulation processes during the transport through the sampling system to the measurement instrumentation (VANCASSEL et al, 2004). The model confirmed that the condensation particles form at the dilutor of the sampling system.…”
Section: Microphysical Propertiesmentioning
confidence: 91%
“…9 A number of experimental 50-52 and theoretical 53,54 studies report that the SO 2 to SO 3 conversion is between 1 and 5%. The aerosol mass spectrometer measurement provides a realistic lower bound on the SO 2 to SO 3 conversion efficiency since the mass spectrometer incompletely detects nucleation mode sulfuric acid and does not detect vapor phase sulfuric acid at all.…”
Section: Emission Indices Of Trace Gases Nonvolatile Pm Andmentioning
confidence: 98%
“…3. The key controlling factors for liquid particle nucleation in the exhaust as identified during combustor exhaust studies are fuel sulphur content, availability of soot surface area which acts as an additional sink for condensable gases, and the temperature drop during exhaust gas dilution and mixing Vancassel et al, 2004;Schneider et al, 2006;Vatazhin et al, 2007).…”
Section: Sulphur Speciesmentioning
confidence: 99%